Religious education and training in developing future human resource professionals : views from experts and teachers - M. Sail, Rahim; Abdul Mutalib, Lukman; Abdul Razak, Nor Ellina; Alavi, Khadijah; Ahmad, Anwar; Tarjo, Shamsul Shah (2011)
The development of human capital focuses not only on acquiring technology and economic knowledge but also focuses on acquiring spiritual, social and political knowledge. Human capital development (HCD) processes relate closely to education and training. An individual who is exposed with technology and economic knowledge infused or integrated with religious education and training would be able to function productively, ethically, able to provide justice and tolerant to diversity of needs, problems and challenges facing a society and/or organization in a borderless competitive markets. The role of Islamic education and training is complementary in developing all-round professionals who are able to balance the demands and challenges of technology, economy, spirituality and quality of life in a developed nation. The main purpose of this study was to explore Islamic religious experts and excellent Islamic teachers’ views on developing future human resource professionals. A qualitative design was employed to explore themes related to the focus of the study among Islamic experts and excellent Islamic teachers. Participants of the study comprised eight (8) Islamic religious experts and 12 excellent Islamic teachers. In-depth interviews with the participants were conducted to gather the data. The findings indicated that Islamic religious experts and excellent Islamic teachers viewed the process and practices of HRD would be greatly strengthened through understanding and application of the contents of the al-Quran and Hadiths and able to apply and practice Islamic concepts and ethics in carrying out HRD functions. Implications that can be drawn from the findings suggest that religious concepts and ethics should be integrated or infused in the pre-service curriculum to prepare for a “balanced” HRD professional. In-service training programs for HRD professionals, on the other hand, should also include religious concepts and ethics to fortify them with the foundations of integrity, professionalism and accountability.